Regulating labour dispatch in China: A cat-and-mouse game - Xiaojun, Feng (China Information, 2019)
This article suggests cautious optimism toward the prevailing Polanyian countermovement discourse by providing a timely and comprehensive examination of the enforcement of the labour dispatch regulation in China. Since the enactment of the regulation, some enterprises have narrowed the remuneration gap between agency workers and formal employees, while others have retained a large gap in overtime pay, bonuses, and welfare benefits between these two groups of workers. The regulation has reduced the number of agency workers, but has invoked the abuse of the more precarious 'outsourced' workers as well. The regulation has had little effect on limiting the use of agency labour to temporary, auxiliary, or substitute positions, raising the requirements of engaging in the labour dispatch business, or stabilizing the employment of agency workers. This article contributes to the extant literature on regulatory enforcement by examining the effects of non-standard employment regulation, highlighting the variance of labour law compliance among enterprises with different types of ownership, and demonstrating how China's ongoing transformation from a planned to a market economy since the 1980s and from high growth to a new normal since 2010 has fundamentally constrained the full implementation of its labour protection regulation.
Development Studies; Oriental Studies
Keywords: China; agency workers; countermovement; employment; labor market; labour dispatch; labour market; labour market regulation; law enforcement; new normal; outsourced workers; precarity

Changing Approaches to Development since 1950: Drawing on Polanyi - Stewart, Frances (History of Political Economy, 2018)
The article focuses on analysis of Karl Polanyi in the book "The Great Transformation" which explained the changes in Great Britain from eighteenth-century mercantilism to nineteenth-century free markets to the state-centered interventionism of the mid-twentieth century evident when he was writing. It mentions additional features needed for understanding the evolution of development thought and repeal of the Corn Laws in 1846, leading to free trade in agricultural products.
Development Studies; Political Science
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; economic development; free enterprise; free trade; mercantile system

The Truncated Commercialization of Microinsurance and the Limits of Neoliberalism - Bernards, Nick (Development & Change, 2018)
Microinsurance — defined as low‐cost insurance products targeting low‐income populations — exemplifies key themes in contemporary neoliberalism, and has figured prominently in neoliberalism's turn to discourses such as 'risk management' and 'financial inclusion'. The development of commercial markets for microinsurance, however, has in practice been highly variable and often very limited. This article considers the implications of this process of 'truncated commercialization'. It draws on a Polanyian analytical framework that emphasizes the contradictory regulatory dynamics involved in the commodification of labour. The article applies this approach by tracing multiscalar efforts to promote microinsurance, examining the emergence of the concept in the efforts of the International Labour Organization to promote social security for informal workers in the 1980s and 1990s, looking at the adoption of explicitly commercializing imperatives in the work of the International Association of Insurance Supervisors in the 2000s, and, finally, considering a case study of South Africa. The truncated commercialization of microinsurance, it is argued, provides a useful lens through which to see the practical impossibility of neoliberal development strategies.
Political Science; Development Studies
Keywords: International Association of Insurance Supervisors; International Labour Organisation; commercialization; microinsurance; neoliberalism; social security

Rethinking the Double Movement: Expanding the Frontiers of Polanyian Analysis in the Global South - Goodwin, Geoff (Development & Change, 2018)
Over the last two decades a rich and diverse body of literature has emerged which uses the ‘double movement’ to analyse social, political and economic change in the global South. The main aims of this article are to expand the boundaries of this scholarship and improve our understanding of how to use the concept to analyse capitalist development in the region. It seeks to achieve this by explaining and extending the original formulation of the double movement, creating a dialogue between scholars who follow alternative readings of the concept, and proposing a revised formulation which builds on the existing literature while moving in new directions. The article concludes by signposting potentially fruitful areas of Polanyian analysis.
Political Science; Development Studies
Keywords: capitalism; commodification; developing countries; development studies; double movement; economic reform; liberalism; political change; social change; social movements

Reconstructing Polanyi? - Levien, Michael (Development & Change, 2018)
Most people read Karl Polanyi today because his critique of laissez faire capitalism seems remarkably applicable to our neoliberal times. Although his late work on ancient and ‘archaic’ economies has enjoyed a consistent specialist readership, Polanyi is best known today for his 1944 magnum opus, The Great Transformation (henceforth GT). Covering a large sweep of mostly European history, the GT seeks to show that the attempt to create a ‘self-regulating market’ was a radical and recent departure from all preexisting economies; that this effort to ‘disembed’ the market from society required a great deal of state planning and force; and that the commodification of the ‘fictitious commodities’ land, labour and money was so socially destructive that it generated countermovements that demanded, and in some measure achieved, social protection. Polanyi termed this whole cycle of disembedding and re-embedding the market the ‘double movement’, and tried to show that it was the underlying cause of the great depression, fascism and two world wars. Given the relentless march of commodification in the neoliberal period and the variety of political responses this has generated (from both the left and far right), many people have been drawn to the idea that we are living through another double movement.
Sociology; Development Studies
Keywords: DALE; Gareth; POLANYI; Karl; 1886-1964; Reconstructing Polanyi: Excavation & Critique (Book); book review; double movement; nonfiction

Latin American Structuralism and Current Financialization - Déniz, José; Marshall, Wesley C. (International Journal of Political Economy, 2018)
In this article, we attempt to update the understanding of the external constraint in Latin America by examining the recent history of the region through the analytical framework of Karl Polanyi in The Great Transformation. As we argue, the greatest force behind today’s external restriction is the financial sector, much as it was a century ago. To reinforce this hypothesis, we provide the reader with relatively new historical material and with arguments made by scholars from diverse backgrounds. Taking into consideration the political and economic structures of Latin America, we argue that the international connections between the elite of the center and the periphery remain the key aspect in understanding today’s complex reality.
Development Studies; Economics
Keywords: Great Transformation; The (Book); Latin America; POLANYI; Karl; 1886-1964; external restriction; financialization; structuralism

Desenvolvimento territorial no Brasil: uma análise a partir da concepção teórica de Karl Polanyi - Waldecy Rodrigues; Nayara Silva Santos (Desarrollo territorial en Brasil: un análisis desde Karl Polanyi., 2018)
This paper analyzes the municipal development in Brazil from the theoretical design of Karl Polanyi. Methodologically, the Polanyi's city development index of Polanyi (IDMP). The results show that according to the concepts analyzed, the Brazilian municipalities, in their majority, have multidimensional incipient features and that there is a direct positive relationship between economic pluralism and quality of life levels. (English)
Development Studies
Keywords: Brazil; abordagem multidimensional; approche multídimensionnelle; city development; desarrollo; desarrollo municipal; desenvolvimento; desenvolvimento municipal; development; developpement; developpement des municipalites; economia plural; economía diversa; enfoque multidimensional; multidimensional approach; plural economy; économie plurielle

The Quest to Bring Land under Social and Political Control: Land Reform Struggles of the Past and Present in Ecuador - Goodwin, Geoff (Journal of Agrarian Change, 2017)
Land reform was one of the most important policies introduced in Latin America in the twentieth century and remains high on the political agenda due to sustained pressure from rural social movements. Improving our understanding of the issue therefore remains a pressing concern. This paper responds to this need by proposing a new theoretical framework to explore land reform and providing a fresh analysis of historical and contemporary land struggles in Ecuador. Drawing on the pioneering work of Karl Polanyi, the paper characterizes these struggles as the attempt to increase the social and political control of land in the face of mounting commodification. The movement started in the 1960s and remains evident in Ecuador today. Exploring land reform in Ecuador from this theoretical perspective provides new insight into land struggles in the country and contributes to debates over land reforms of the past and present elsewhere in the Global South.
Political Sciences; Development Studies
Keywords: Ecuador; commodification; land markets; land reform; reforms; social movements

Urban Governance in Africa Today: Reframing, Experiences, and Lessons - Obeng-Odoom, Franklin (Growth & Change, 2017)
Progress in analysing the instrumental view of governance as an engine for growth, poverty reduction, and inclusive development has been held back by the difficulty in framing governance. This essay seeks to address this problem by 1) reframing urban governance 2) evaluating its aims, processes, and outcomes, and 3) explaining those outcomes on the basis of which some lessons are teased out. Using examples from Africa and an institutional political economy approach (based on institutional economics, Marxist political economics, Georgist political economics, and Polanyian political economy), I show that, overall, while urban economies are growing; both urban poverty and inequality levels have risen substantially. Urban governance has paved the way for new forms of urban development that only benefit the few. Not only are there differences in how urban services and resources are experienced, accessed, and controlled but the varieties are also socially differentiated. I argue that the underlying reasons for this disjuncture between 'urban governance' in theory and 'actually existing urban governance' are 1) difficulties in implementing urban governance theory consistently in practice, 2) problems arising because urban governance theory has been implemented in practice, 3) tensions that would entangle most policies which do not address historical and structural economic issues, 4) restrictive assumptions, and 5) incoherence among the different dimensions of urban governance. To resolve these contradictions, I put the case for major structural and institutional change involving: 1) the re-ordering of the roles of the state, market, and society as institutions of change; 2) re-working the relationships that bind together land, labour, capital, and the state, and 3) re-organising the channels for keeping the attainment of the ends of urban governance in check.
Development Studies
Keywords: Africa; economic development; economic policy; labor; labour; poverty reduction; public administration

State–peasant movement relations and the politics of food sovereignty in Mexico and Ecuador - Henderson, Thomas Paul (Journal of Peasant Studies, 2017)
This contribution argues that the articulation between the state and peasant organizations’ internal structures – the class characteristics of their mass bases, their leaderships and the modes of interaction between the two – is critical for determining the nature of contemporary struggles guided by the discourse of food sovereignty. It will show that that counter-hegemonic demands are not synonymous with counter-hegemonic practice; rather than struggling to replace the neoliberal food regime, many peasant organizations employ the food sovereignty discourse as a political tool in their negotiations with the state in order to access resources from within the prevailing neoliberal model, not to transform it.
Development Studies
Keywords: GRAMSCI; Antonio; 1891-1937; Via Campesina; agriculture & state - Ecuador; agriculture & state - Mexico; food regime; food sovereignty; hegemony; peasant organizations; peasant studies

Towards Another 'Great Transformation' - Mkandawire, Thandika (Africa Insight, 2016)
As Karl Polanyi indicates in the 'Great Transformation',1'the so-called self-regulating markets cannot exist for any length of time without destroying human society'. Three 'Great Transformations' have taken place. The first occurred in Europe at a time when it was widely believed that markets were nature's way of managing exchange in an efficient way and that interference in the workings of the market, as Adam Smith argued, was not only artificial, but against the laws of God.2 The second was about society's reaction in defending itself against the ravages of the market. The third was when neoliberalism launched a counter-movement that gave the market primacy. This paper argues that the assumption that the self-regulation expected from 'corporate social responsibility', or the instinct for self-preservation, would replace the state, had failed disastrously. The neoliberal model is therefore in trouble. It is important to contemplate a new global order that will be built on and facilitate social orders that are developmental, socially inclusive and democratic - which will be the fourth 'Great Transformation'. As the paper argues, there are two imperatives: the first imperative would be the creation of global institutions that would ensure that commitments to justice, equality and democracy are translated into global and national policies; and the second one would be the intellectual and ideological challenge of the views and discursive practices that, all too often, fetishised globalisation into some exogenous force that ineluctably imposes its laws on the human race.
Economics; Development Studies
Keywords: Africa studies; Europe; democracy; economic conditions; humanism; justice administration; socioeconomics

The limits to China's non-interference foreign policy: pro-state interventionism and the rescaling of economic governance - Gonzalez-Vicente, Ruben (Australian Journal of International Affairs, 2015)
China's foreign policy has been long committed to a principle of non-interference in the internal affairs of sovereign countries. While one could easily point out past and present-day inconsistencies in its implementation, this article argues that defenders and critics of the principle both rely on a limited interpretation of ‘interference’ or ‘intervention’ based on an ideology of Westphalian sovereignty. Particularly problematic is the conceptual distinction between the ‘political’ or ‘diplomatic’, on the one hand, and the ‘economic’, on the other. As Polanyi's concept of embeddedness reminds us, markets, society and politics occur simultaneously, and can only act as discrete realms in epistemological abstractions. It is thus argued that non-interference is a semi-formal institution that governs China's diplomatic engagements and affects its economic activities. While the totality of China's interactions with the world has diverse and sometimes contradictory impacts on global governance, non-interference itself has apparent consequences for the rescaling of regional economic governance. Specifically, this article contends that Chinese non-interference results in the empowerment of political elites at national levels, and thus in the (re-)emergence of the nation state as a gatekeeper and facilitator of the advancement of capitalist enterprises. As a result, through non-intervention, China's foreign policy undermines supranational regulatory approaches and fosters state-based regional architectures.
Development Studies; International Relations
Keywords: China; China - foreign relations; People's Republic of China; Westphalians - foreign countries; bilateralism; economic policy; embeddedness; foreign policy; non-interference; socioeconomic theory; supranationalism

Introduction: The ‘Labour Question’ in Contemporary Capitalism - Chhachhi, Amrita (Development and Change, 2014)
The recent upsurge in workers’ struggles globally has bought labour again to the forefront, despite predictions that the working class was no longer relevant as a force for social transformation. Neoliberal globalization, with the hypermobility of capital, has led to the emergence of new forms of flexible work/labour, the co-existence of old and new working classes, and an extreme rise in inequality, realigning class structures nationally and globally. Financialization has ushered in a new regime of accumulation and there is a deepening crisis of reproduction. Can a Marx plus Polanyi theoretical integration capture contemporary dynamics of capitalist globalization and the role of labour? What do the trajectories of such struggles in the South tell us about the limits and potentialities for a counter-capitalist movement? More crucially, is the route to full social citizenship entitlements still possible via employment (with its further extension universally), or is it to be reached by directly demanding citizenship rights, bypassing labour-based demands? How do recent collective actions express workers’ interests/identities as workers, citizens and consumers? What role is the state playing in responding/mediating/facilitating these struggles? The Introduction delineates some of these contentious issues which frame this Forum Debate. The contributors all offer different perspectives and critical insights on the connections between forms of labour, possibilities for action and organization, the relationship between labour struggles and social citizenship and the role of the state in contemporary capitalism. The conclusion reflects on some of the equally controversial proposed alternatives and argues for going beyond minimalism and for the imperative of radical rethinking to ensure dignified work and full social citizenship entitlements as part of a new social emancipatory political project.
Development Studies
Keywords: MARX; Karl; 1818-1883; capitalism; globalization; labor question; labour question; neoliberalism

Capital–Labour and State Dynamics in Export Horticulture in North-east Brazil - Selwyn, Ben (Development and Change, 2014)
This article argues for the primacy of class relations and struggles as determinants of developmental processes and outcomes, emphasizing the evolving, dialectical nature of these relations. It does so by providing a case study of export horticulture in North-east Brazil. It documents how the region's rural trade union has been able, through mobilizing its membership base, to achieve significant improvements in their livelihoods, pay and conditions. It also shows how the region's employers have responded to these gains by restructuring the labour force in order to attempt to fragment and weaken it. The article pays particular attention to the gender dynamics of class relations.
Development Studies
Keywords: Brazil; Polanyian approaches; class relations; development

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Economics; Development Studies
Keywords: Great Transformation; The (Book); primitive societies

The Mystery of Capital or the Mystification of Capital? - Obeng-Odoom, Franklin (Review of Social Economy, 2013)
In contemporary political economic analyses of development processes, Hernando De Soto'sThe Mystery of Capital, has been one of the most discussed, albeit controversial, books. Although well received by global development agencies such as the World Bank, a key exponent of De Soto's work, positing that the creation and institutionalisation of individual property in housing and land revives “dead capital” and creates the conditions that will enable the poor to emerge from abject poverty, has been widely criticised. These criticisms show that (1) the thesis is flawed, (2) the flaw is due to implementational problems and (3) the practical implications arising from the thesis are largely neutral and will neither improve nor worsen poverty. Although agreeing with the first criticism, this paper argues that the second critique must be nuanced, and the third is entirely mistaken. Utilising insights from Joseph Schumpeter, Karl Polanyi and Henry George, it makes the case that applying De Soto's ideas through policy would be ineffective in curbing urban poverty, and actually serve to simultaneously entrench and augment it. Moreover, while finding that De Soto's assumption that the poor possess some economic agency is sound and may, indeed, secure socially beneficial outcomes through pursuing innovative and entrepreneurial endeavours, De Soto's conception of such processes remains largely emasculated from broader political economic considerations.
Development Studies
Keywords: dead capital; economic research; fictitious commodities; fictitious commodity; political economic analysis; poverty; progress amid poverty; property; social innovation

Promoting Freedom of Association in China? Putting Transnational Corporate Social Responsibility into a National Context - Chan, Chris King-Chi (Journal of Comparative Asian Development, 2013)
Using the findings of an intensive case study of a corporate social responsibility (CSR) project in China, this paper argues against the view that CSR and the state's regulations are mutually exclusive. It contests that the theorization of the transnational social movement (TSM) should not ignore the development of the state regime, which in turn is shaped by the power relations in the workplace and the community, and is embedded in the national political history. The findings of this research support the Polanyi-inspired approach which sees CSR as being embedded in the changing patterns of business–government–society relations. This approach highlights that the behaviour of the state and the engagement of civil society have actively shaped the scope and the implementation of CSR. Following this line of argument, this paper provides evidence of the dynamics and paradox of workers' and grassroots NGOs' engagement in CSR in China. The specificity of China stems from the state, on the road of China's transition from a state socialist country to being a part of global capitalism. Workers' and NGOs' frustration at the denial of freedom of association (FOA) under the CSR projects at this stage reflects well the legacy of Chinese state socialism, in particular the nature of the official trade unions and the suppressive function of the local state–global capital nexus. Therefore, the state is by no means being excluded from either business or civil society, as the orthodox view of CSR presumes.
Development Studies
Keywords: CSR; China; NGOs; corporate social responsibility; delegated legislation; freedom of association; labor unions; labour unions; migrant labor; migrant labour; migrant workers; nongovernmental organizations; social responsibility of business; workers’ committee

China's Decentralized and Inegalitarian Developmental State - Nordhaug, Kristen (Forum for Development Studies, 2012)
This article investigates China's market reforms and rapid economic development from the late 1970s. The following questions are posed: (1) How did the Chinese 'peasant revolution' and the rural policies and institutions of Mao China influence the market reforms and subsequent economic development? (2) How does China's development after the market reforms relate to Marxist and Polanyian notions of proletarization and commodification of land and labour as preconditions of capitalist development? (3) To what extent and why does China's development after the market reforms diverge from East Asian growth with equity? (4) How does China's 'decentralized developmental state' influence its growth model and distribution? (5) The present Chinese government tries to promote greater equality and more domestic consumption. Is this a Polanyian 'double movement' in response to commodification of land and labour? How likely are these policies to succeed? These questions are addressed through historical-comparative analyses with comparisons of long-term rural dynamics of Mao China and the former Soviet Union. China after the market reforms is compared with England during its transition to agrarian capitalism and industrial capitalism from the sixteenth century through the early nineteenth century and with Taiwan and South Korea from the late 1940s until the 1980s.
Development Studies; Economics
Keywords: Marxian; Sraffian; aggregate factor income distribution; current heterodox approaches: socialist; inflation; institutions and growth; institutions: design; formation; and operations; macroeconomic analyses of economic development; money; socialist systems and transitional economies: national income; product; and expenditure; structure; scope; and performance of government

Les sociétés civiles entre risques ploutocratiques de la philanthropie et alternatives solidaires : une lecture polanyienne, The civil societies between the plutocratic risks of philanthropy and solidarity based alternatives : a Polanyian reading - Servet, Jean-Michel (Mondes en développement, 2012)
Tant dans les pays du Nord que dans ceux du Sud, un compromis entre une logique néo-libérale anti-étatiste et certains intérêts des organisations non gouvernementales a marqué la construction des sociétés civiles. Il s’est réalisé notamment à travers le social business soutenu par de grandes entreprises. En mobilisant le concept polanyien de principe d’intégration économique, l’analyse a pour ambition de comprendre les limites de ce nouveau modèle de philanthropie et ce qui le différencie de l’économie solidaire., Both in the Norths and in the Souths, a compromise between a neoliberal anti-statist logic and interests of non governmental organizations marked the construction of civil societies. This is achieved particularly through the social business supported by big companies. By mobilizing the polanyien concept of principle of economic integration, the analysis aims to understand the limits of this new model of philanthropy and what differentiates it of the solidarity based economy.
Development Studies
Keywords: NGOs; Polanyi; formal and informal sectors; institutional arrangements; nonprofit institutions; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; principes d'intégration économique; shadow economy; social business; économie solidaire

Solidarity Economy in Brazil: Movement, Discourse and Practice Analysis Through a Polanyian Understanding of the Economy - Lemaître, Andreia; Helmsing, A. H. J. (Bert) (Journal of International Development, 2012)
Solidarity economy (SE) initiatives constitute a worldwide phenomenon that is today at the heart of numerous economic and social debates. They are active in very diverse economic sectors, aiming for example to create employment for poor and low-qualified workers. We begin with presenting a Polanyian framework for the analysis of such economic activities, which enables us to develop a plural and integral conception of a productive organisation. We draw on Polanyi's thesis that economy is a political and institutionalised process and present a historic overview of the construction of the SE ‘sector’ in Brazil. We put forward the hypothesis that the SE today in Brazil represents a social movement. Then, we ask ourselves if the SE movement led to a change in grassroots economic initiatives, such as ‘people's cooperatives’. We present the results of exploratory research undertaken on 15 people's cooperatives in the State of Rio de Janeiro and its conclusions. Copyright © 2012 John Wiley & Sons, Ltd.
Political Science; Development Studies
Keywords: Brazil; inclusion; international development; local development; people's cooperative; social movement; solidarity economy

Economic and Ecological Crises: Green new deals and no-growth economies - Jessop, Bob (Development, 2012)
Bob Jessop applies cultural political economy to the global economic and ecological crisis. He presents theoretical preliminaries concerning economic and ecological imaginaries, and then goes on to highlight the multidimensional nature of the current crisis and struggles over its interpretation.
Sociology; Development Studies
Keywords: cultural political economy; ecological imaginary; economic imaginary; finance-dominated accumulation; finance-led accumulation; green new deal; neoliberalism; post-neoliberalism

The global financial crisis of 2008–2009: an opportunity for development studies? - Copestake, James (Journal of International Development, 2010)
This paper draws upon the five other papers presented in this volume, along with other presentations made at the 2009 Development Studies Association Conference, to reflect on the relationship between development studies and the 2008–2009 global financial crisis. It first analyses antecedents to the crisis by relating the papers presented by Gore (on long waves of capitalism) and Fischer (on China's integration into the world economy) to a Polanyian analysis. It then considers immediate policy responses with particular reference to India (based on the conference presentation by Mehrotra), China (based on the paper by de Haan) and the 2009 DFID White Paper. Third, it considers two possible additional sources of finance for developing countries: South Korean aid (discussed by Chun et al.) and new forms of international money (discussed by Hudson). The paper concludes that while the crisis is a reminder of structural global economic interconnectedness a challenge for development studies is to combine this fact with analysis that is also interdisciplinary, multi-tiered and policy relevant. Copyright © 2010 John Wiley & Sons, Ltd.
Development Studies
Keywords: 2009 DFID White Paper; China; capitalism; development economics; development studies; global financial crisis; international development; international economic integration

Power and Progress: The Swing of the Pendulum - Stewart, Frances (Journal of Human Development & Capabilities, 2010)
This paper uses Polanyi's 1944 analysis of policy change—in which there are long-term swings from state regulation to markets and back again, as the consequences of one regime lead to political reactions that in turn reverse the policies. It shows how the Polanyi analysis continued to apply throughout the twentieth and early-twenty-first century, well beyond when he wrote, and that the swings also apply to developing country policy-making. It argues that there are new signs of policy change—this time against market domination—in a number of developing countries. The paper concludes that Polanyi's view of the conditions behind policy change—notably long-term political movements, political struggle and political conflict—needs to be introduced into the analysis of policy change for the promotion of human development and the expansion of capabilities.
Development Studies; Economics
Keywords: developing countries; government policy; human development; legislation; policy sciences; policy swings; political economy; political planning

Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire - Servet, Jean-Michel (Revue Tiers Monde, 2010)
English translation: Karl POLANYI has an indirect understanding of the societies that were part of the Third World in the fifties. From anthropologists he came out with the principle of reciprocity. He then opposed this principle of economic integration to both redistribution and market principles. Reciprocity can neither be viewed as a practice of primitive societies (as in evolutionist approaches) nor as a gift and counter-gift exchange. Reciprocity needs to be understood as a social whole and through a claimed mutual dependency. In this approach, reciprocity allows to set up the definition of the solidarity-based economy. Jean-Michel Servet, “ Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire ”, Revue Tiers Monde 2/2007 (n° 190) , p. 255-273
Development Studies
Keywords: reciprocity

Relaxing the shackles: The invisible pendulum - Stewart, Frances (Journal of International Development, 2009)
This note draws on Polanyi's pendulum in economic policies presented in the the Great Transformation—with swings back and forth between strong restrictions on the market and market domination, each resulting from excesses of the dominant model. The swing he described, when he wrote, was a reaction to the consequences of market domination, notably the Great Depression, and ushered in Keynesianism and the welfare state. In the late twentieth century, there was a swing back towards the market as a result of the inefficiencies associated with this interventionism. This note argues that the pendulum is swinging again, following the political and economic consequences of this market domination. Again market forces are being restrained by regulation, state takeovers, social protection and Keynesian macro-policies, while environmental factors have added to pressures for interventionist policies. Copyright © 2009 John Wiley & Sons, Ltd.
Development Studies; Economics
Keywords: Polanyi; interventionism; markets; pendulum

Sociopolitical sustainability – the pendulum at globalisation's frontiers - Boutilier, Robert (Keeping Good Companies (14447614), 2009)
The article explores the potential roots of the unsustainability of the intersectoral dynamic. Political economist Karl Polanyi stresses that excesses of globalisation led to the unsustainability among the private, public and civic sectors. The backlash against globalisation and the private sector has its roots in the imbalance among the three sectors. The impact of the absence of regulatory regimes on globalisation's frontiers on the private sector is discussed, as well the process by which companies help stabilise their partners.
Development Studies
Keywords: economic sectors; globalization; international relations; private sector; sustainability

Drivers of development over the next 30 years: Some speculations - Harriss, John (Journal of International Development, 2009)
Class relationships are amongst the fundamental drivers of development, and it is argued here that over the next 30 years a major influence on the pattern and path of development will be exerted by the rise of the ‘new middle classes’ of Asia. At the same time, in the context of the blocked transition of the present, it seems unlikely that those who are marginalised and excluded will be able adequately to organise resistance, much less change structures of power, but poverty will be managed through welfare interventions like India's National Rural Employment Guarantee Scheme. Copyright © 2009 John Wiley & Sons, Ltd.
Political Science; Development Studies
Keywords: Asia; India; double movement; eastern hemisphere; economic development; middle class; new middle class; social change; social classes; social structure

Development's invisible hands: Introduction to special issue - Thomas, Alan; Sumner, Andy; Tribe, Michael (Journal of International Development, 2009)
This Special Issue comes from the Development Studies Association (DSA) 30th Anniversary conference in 2008. The theme was ‘Development's Invisible Hands’, focusing on the forces likely to influence global change and re-shape development agendas over the next 30 years. The first section comprises brief invited thinkpieces mainly from DSA past presidents. Interestingly, while some focus on Adam Smith's original ‘invisible hand’ analogy and others discuss a range of non-market issues, several invoke Karl Polanyi on the limitations of market society. The second and third sections consist, respectively, of ‘synthesis’ papers on parallel panel themes and papers developed from the best panel presentations. The papers demonstrate the range of issues raised by questioning the future of development and development studies—while the limitations of future gazing are pointed up by the unexpected challenge to current development models presented since the conference by the global financial crisis. Copyright © 2009 John Wiley & Sons, Ltd.
Development Studies
Keywords: Development Studies Association; POLANYI; Karl; 1886-1964; SMITH; Adam; 1723-1790 - political & social views; development economics; development studies; economic development; futures; invisible hand; mathematical models of economics

Karl Polanyi's Legacy - Hart, Keith (Development and Change, 2008)
Click on the article title to read more.
Anthropology; Development Studies
Keywords: biography

The Poverty of the Global Order - Da Costa, Dia; Mcmichael, Philip (Globalizations, 2007)
This paper argues that the legitimacy of the global order depends not on economic progress alone, but on the progressive naturalization of its epistemological foundations, through 'new solutions' to old problems by states and development agencies. New solutions become methods of social control through which the dominant visions of what count as viable futures are reproduced. We critique efforts to humanize development (e.g., by the World Bank, Amartya Sen) as evidence of development's epistemological crisis. Deploying Karl Polanyi's distinction between formal and substantive economy, we consider examples of substantive economy, which realize equality through strategic sovereignty and representational power, in collective and individual terms. These represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects development studies and international relations. Este documento sostiene que la legitimidad del orden global no depende solamente del progreso económico, sino de la naturalización progresiva de sus fundamentos epistemológicos, a través de 'nuevas soluciones' a problemas antiguos mediante estados y agencias del desarrollo. Las nuevas soluciones se convierten en métodos de control social, a través de los cuales se reproducen las visiones dominantes de lo que cuenta como futuros viables. Criticamos los esfuerzos de humanizar al desarrollo (p.e. Banco Mundial, Amartya Sen) como evidencia de la crisis del desarrollo epistemológico. Utilizando la distinción de Kart Polanyi entre economía formal y economía sustancial, consideramos ejemplos de una economía sustancial, la cual realiza la igualdad por medio de una soberanía estratégica y un poder representativo, en términos colectivos e individuales. Estas, entre otras iniciativas, representan 'espacios de esperanza' prácticos y epistemológicos para criticar la crisis de la epistemología de mercado que infecta a los estudios de desarrollo y las relaciones internacionales.
Developent Studies; Sociology
Keywords: formal economy; international law; international relations; international trade; social control; social epistemology; sovereignty; substantive economy

The role of the UN Millennium Declaration and of the World Economic and World Social Forum for Structural Change - Abrahamson, Hans (Conference Papers – International Studies Association, 2005)
Globalisation can in a polanyian sense be understood as a double movement. Societal reaction to the shortcomings of the corporate driven process of globalisation from above (the first movement) creates a counter movement from below (the second movement). The relations between different actors within the political landscape and the area of tensions between the two movements are characterised by the gramscian war of position and its power struggle over the hegemonic discourse. At times the constellation of political forces permits an institutionalised state of equilibrium built on converging interests between different social forces. During the Westphalia era with its nation-state project the social contract constituted the base for such an historic compromise. The end of the cold war and strengthened process of corporate globalisation has eroded the base for this social contract on a national level increasing development gaps not only between countries but also within countries. This paper addresses the question of room for manoeuvre for structural change in order to deal with present challenges within the Global Political Economy. It discusses how possibly the UN Millennium Declaration could be used in the ongoing discursive war of position between actors at the World Economic Forum in Davos (representing the first movement) and actors at the World Social Forum in Porto Alegre (representing the second movement) in order create a social base for a new social contract albeit on the global level. Such a discussion also illustrates present potential of these arenas in contributing to a future global political economy of peace and development.
Peace Studies; Development Studies
Keywords: United Nations; World Economic Forum; economics; forums (discussion & debate); globalization; hegemony; political science

And if there was no state?: critical reflections on Bates, Polanyi and Evans on the role of the state in promoting development - Menocal, Alina Rocha (Third World Quarterly, 2004)
The article review three books about the role of the state in promoting development. It includes "Markets and States in Tropical Africa: The Political Basis of Agricultural Policies," by Robert Bates, "Embedded Autonomy: States and Industrial Transformation," by Peter Evans and "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Political Science; Development Studies
Keywords: BATES; Robert H.; 1942-; EVANS; Peter; 1944-; Embedded Autonomy: States and Industrial Transformation; Great Transformation; The (Book); Markets & States in Tropical Africa: The Political Basis of Agricultural Policies (Book); nonfiction; state development

Third Worldism and the lineages of global fascism: the regrouping of the global South in the neoliberal era - Patel, Rajeev; McMichael, Philip (Third World Quarterly, 2004)
We come to an analysis of Third Worldism through an historical understanding of the development project, one that locates Third Worldism as a moment in a broader series of resistances both to capital and colonialism, and to the techniques used by the state to maintain hegemony. Viewing Third Worldism in this wider context, we argue, enables us to not only explain the failure of Third Worldism to deliver on its vision of emancipation from colonialism, but to also explain the shape of contemporary resistance to the world capitalist order. We argue that the theory and practice of development depends on a certain biopolitics, rooted in a regime of sovereign state control, and designed to mobilise citizens in ways favourable to capital. We hold that Third Worldism embraced this form of sovereignty and its biopolitics. Further, by blending cultural studies analysis with a Polanyian interpretation of the rise of fascism, we argue that Third Worldism can be situated as a moment in the maturation of 'global fascism'. Finally, we argue that contemporary resistances to neoliberalism have recognised the complicity of the state with capital. These 'new internationalisms' arise from the ashes of Third Worldism, with an altered understanding of 'sovereignty' that challenges the trajectory of the Third World sovereign state.
Sociology; Development Studies
Keywords: biopolitics (sociobiology); capitalism; colonies; fascism; global capital; global fascism; hegemony; liberty; sovereignty (political science)

Discourses on peace and development - Hettne, B. (Progress in Development Studies, 2001)
Assuming a close relationship between peace and development, this paper analyses a succession of schools of thought in development forming part of three distinct, historically contextualized development and security discourses: the industrialization imperative in the emerging state-system in nineteenth-century Europe, the international concern with global poverty in the bipolar post second world war world and the current meaning of development in a globalized and increasingly chaotic world. The third of these discourses contains major challenges for development theory. The discourses are related to great transformations in political economy, understood in Polanyian terms as tensions between market expansion and societal response.
Peace Studies; Development Studies
Keywords: conflict; development theory; discourse; economic development; market expansion; peace; peace - economic aspects; security

On Polanyi - Munck, Ronaldo (Area Development and Policy, 2021)
Karl Polanyi provides a rich repertoire of concepts to build a critical understanding of the world of globalization and alternatives to the status quo. In reviewing two recent collections around the work of Polanyi, we show some of the concepts that might be developed in terms of ‘using Polanyi’. This would include his inspired double-movement concept and the way he dealt with non-capitalist societies. Polanyi is as relevant for the so-called developing societies as he is for the advanced industrial societies where he has garnered most attention.
Publisher: Routledge _eprint: https://doi.org/10.1080/23792949.2020.1830708
Keywords: Polanyi; double movement; globalización; globalization; movimiento doble; no capitalista; non-capitalist; Поланьи; глобализация; двойное движение; некапиталистический.; 全球化; 双重运动; 波兰尼; 非资本主义

Território e Desenvolvimento em Karl Polanyi: uma revisão sistemática - Rodrigues, Waldecy; Camargo, Wainesten (Redes, 2020)
This paper consists of a systematic review of the literature on territorial economic development from the perspective of Karl Polanyi's works. For this, a protocol was created to order the selection of scientific articles, after this step, an analysis of the main works that used Karl Polanyi ideas, on the perspective from territorial development, in a central way in their approaches was performed. The main databases used were SCOPUS, WEB OF SCIENCE and SCIELO, from 1990 to 2018. About 100 (one hundred) papers were found that met the protocol of the systematic review. All these works have been read and their details and characteristics can be found in this text. It was identified that Karl Polanyi has a classical approach to territory, and his most discussed ideas are the double movement, embeddedness, and economic history. The main results point to the strength of Karl Polanyi thought in research on development in several territorial scales, allowing to think these issues in interdisciplinary and plural terms.
Development Studies
Keywords: desenvolvimento; development; systematic review; territorial development; território

Karl Polanyi and substantivism in economic development - Rodrigues, Waldecy; Santos, Nayara Silva Dos (Brazilian Journal of Political Economy, 2020)
ABSTRACT A reading of Karl Polanyi’s work gives us a broader and more plural view of the development process beyond the exclusively economic dimension. This scientific text aims to recover the theoretical contribution of Karl Polanyi and its contribution to the understanding of the development process from a plural and substantive conception of economy. The key lesson learned in this research is that regardless of a country’s economic system, one should pay attention to the existing institutional variety and complexity of its cultural and social mosaic. True development will only be achieved if it is structured with effective public policies in order to promote this heterogeneity to the maximum possible social welfare.
Publisher: Centro de Economia Política
Keywords: Economic development; Karl Polanyi; plural economy